2008
DOI: 10.1017/s1047951108003181
|View full text |Cite
|
Sign up to set email alerts
|

A practical and transferable new protocol for treadmill testing of children and adults*

Abstract: Until puberty, boys and girls have the same indicators of exercise performance. Subsequent to puberty, uptake of oxygen and distance run differ, with males showing higher uptake of oxygen. There is still an age-dependent dynamic of peak uptake of oxygen related to body surface area. Using these new reference values, covering the whole range of age, it proves possible to compare performance during growth and aging of the individual. In this fashion, we have calculated centiles for all recorded variables. Extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 19 publications
(43 reference statements)
3
44
0
Order By: Relevance
“…In a comparison of the normative curves established for TTE in the present study with those provided by Dubowy et al, 29 similar patterns were obtained. In boys, the normative curve for TTE on the FTT showed an almost linear increase with age.…”
Section: Normative Values For the Fitkids Treadmill Testsupporting
confidence: 86%
See 1 more Smart Citation
“…In a comparison of the normative curves established for TTE in the present study with those provided by Dubowy et al, 29 similar patterns were obtained. In boys, the normative curve for TTE on the FTT showed an almost linear increase with age.…”
Section: Normative Values For the Fitkids Treadmill Testsupporting
confidence: 86%
“…In girls, the increase in TTE on the FTT started to level off at approximately 10 years of age. The endurance time achieved by male participants in the study of Dubowy et al 29 increased until the age of 19 years, whereas in female participants it decreased continuously from puberty. Van der Cammen-van Zijp et al 30 and Binkhorst et al 32 also obtained similar patterns.…”
Section: Normative Values For the Fitkids Treadmill Testmentioning
confidence: 86%
“…The expression of peak V O 2 as an absolute value, rather than as a percentage of predicted normal value based on sex and age, might explain this finding, particularly because there is an overall trend for increasing peak V O 2 (in mL ⅐ kg Ϫ1 ⅐ min Ϫ1 ) in the young. 17 Similarly, Das and colleagues 18 showed that only 21% of children on the waiting list for HTx have a peak V O 2 below the 14 mL ⅐ kg Ϫ1 ⅐ min Ϫ1 cutoff currently used to recommend HTx in adults. Their small study also showed that the use of absolute peak V O 2 value (in mL ⅐ kg Ϫ1 ⅐ min Ϫ1 ) can be misleading in children because of differences in body size and muscle mass.…”
Section: Clinical Utility Of Peak V O 2 %mentioning
confidence: 99%
“…Sir, The article of Dubowy et al 1 provides reference values for maximal exercise performance evaluated by a simple treadmill test in a population ranging from 4 to 75 years of age, classified according to gender and age both with and without relation to body mass and body surface area. The purpose deserves attention, especially in view of the increasing group of adults with congenital cardiac disease, whose exercise capacity requires a comparison with normal values.…”
mentioning
confidence: 99%
“…Dubowy et al 1 rely on body mass, thus admitting an undue significance to the fat component of the body, as lean body mass is not at hand. The use of body mass as a reference parameter for cardiovascular performance may thus turn out to be a method that, indirectly, estimates overweight.…”
mentioning
confidence: 99%